Pengaruh Harga, Citra Merek Dan Word Of Mouth Terhadap Keputusan Pembelian Di PT Traveloka (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Hanin, Jilan; Rizal, Muhammad; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Price, brand perception, and word of mouth are the variables that will be studied in this study. Quantitative research methods were used in this study. Probability sampling using a purposive sampling methodology is the sampling method employed. Multiple linear regression methods were used in the data analysis conducted using SPSS 29. The study's findings reveal that at PT Traveloka, customers are swayed by pricing, brand image, and word of mouth when making purchases. Keywords : Price, Brand Image, Word Of Mouth, And Purchasing Decision